The Effect of Visual and Manipulative Learning Media on Elementary School Students’ Conceptual Understanding of Integers: A Quasi-Experimental Study - Putri Siregar, Yusfika Nayla (Sekolah Tinggi Agama Islam Kuningan, 2026)
Backround: Many elementary school students experience difficulties in understanding integer concepts, particularly negative numbers, due to the abstract nature of the topic and reliance on conventional teaching methods that emphasize procedural memorization over conceptual understanding.Objectives: This study aims to examine the effect of visual and manipulative instructional media on fifth-grade elementary school students' conceptual understanding of integer concepts.Method: A quantitative approach with a quasi-experimental design using a nonequivalent control group design was employed. The participants, fifth-grade students at an elementary school in Indonesia, were divided into an experimental class and a control class. The experimental class received instruction using visual and manipulative media, while the control class received conventional instruction. Data were collected through pre-test and post-test instruments and analyzed using an independent sample t-test.Findings and Implications: The experimental class experienced a significantly higher improvement in conceptual understanding compared to the control class (t = 2.87, p < 0.05), with mean gain scores of 26.8 and 12.4, respectively.Conclusion: The use of visual and manipulative instructional media can effectively enhance elementary school students' conceptual understanding of integers. Teachers are encouraged to integrate number line representations and concrete manipulatives as part of a sequential instructional approach in mathematics learning.